Price versus clinical guidelines in primary care statin prescribing: a retrospective cohort study and cost simulation model. (March 2022) - De Zarate, Matias Ortiz; Mentzakis, Emmanouil; Fraser, Simon DS; Roderick, Paul; Rutter, Paul; Ornaghi, Carmine
Objective: To investigate the relative impact of generic entry and National Institute for Health and Care Excellence clinical guidelines on prescribing using statins as an exemplar. Design: Retrospective analysis of statin prescribing in primary care and cost simulation model. Setting: Royal College of General Practitioners Research and Surveillance Centre (RCGP R&SC) database and Prescription Cost Analysis (PCA) database. Participants: New patients prescribed statins for the first time between July 2003 and September 2018. Main outcome measures: Shares of new patients prescribed one of the five statins available in the British National Formulary, and cost of prescribing statins to new and existing patients in primary care in England. Results: General trends of statin' prescriptions were largely driven by a decrease in acquisition costs triggered by patent expiration, preceding NICE guidelines which themselves did not seem to affect prescription trends. Significant heterogeneity is observed in the prescription of the most cost-effective statin acrossGPs. A cost simulation shows that, between 2004 and 2018, the NHS could have saved £2.8bn (around 40% of the £6.3bn spent on statins during this time) if all GP practices had prescribed only the most cost-effective treatment. Conclusions: There is potential for large savings for the NHS if new and, whenever possible, ongoing patients are promptly switched to the first medicine that becomes available as generic within a therapeutic class as long as it has similar efficacy to still-patented medicines.